STRATEGI PENGEMBANGAN DESA WISATA SEBAGAI MODEL PEMBERDAYAAN MASYARAKAT DI DESA BUDAYA PAMPANG SAMARINDA UTARA - Siti Nur Djubaedah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
The background of this research is the existence of a strategy to develop a tourist village in Samarinda's Pampang Cultural Village which will have a good impact on the economy of Samarinda's Pampang Cultural Village community. The Pampang Cultural Village in Samarinda has been developed by the government and the local community as a tourist destination, so it is necessary to know the strategy of developing a tourism village in Samarinda's Pampang Cultural Village so that the human resources we have must be utilized properly and increase tourist arrivals. Grand Theory in this research is the principles of managing the development of tourism villages by Gumelar (2010), among others, utilizing the facilities and infrastructure of the local community, benefiting the local community, involving the local community, and implementing the development of rural tourism products. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results showed that with the development of a tourism village development strategy in Samarinda's Pampang Cultural Village to further develop through the human resources that we have and can be managed properly, as well as providing an economic impact on the community of Pampang Cultural Village such as changes in the economic activities of its people who get additional income in activities tourism. From the results of the study it is suggested to the government in the development of tourism the government should build tourism education, and improve facilities and infrastructure as well as recreational facilities even better in the cultural objects of the Pampang Cultural Village in Samarinda.